The Effectiveness of Group Therapy based on Acceptance and Commitment on Emotional Eating, Body Image and Rumination of Overweight Female Students - Shahrazad Naghashzadeh; Ahmad Amani (مطالعات روانشناختی)
The aim of this study was to determine the effectiveness of acceptance and commitment group therapy on emotional eating, body image and rumination of overweight female students. The current research was semi-experimental and in the form of a two-group pre-test-post-test design with a 2-month follow-up. The population of this research is all overweight teenage students (13 to 17 years old) who were introduced to obesity treatment centers in Borujerd city by school health educators; A sample of 30 people was selected voluntary sampling and randomly divided into two groups of 15 people. The instruments were the rumination scale questionnaire by Nolen-Hoeksma, the multidimensional body-self relationship questionnaire by Bern et al., and Stein's eating behavior questionnaire. The experimental group received 8 sessions of acceptance and commitment group therapy. Analysis of covariance test was used to analyze the data. The results of the research showed that group therapy based on acceptance and commitment has a significant effect on emotional eating, self-image and rumination of overweight female students. Therefore, group therapy based on acceptance and commitment can be used as a new therapeutic approach in improving emotional eating skills, self-image and rumination of overweight female students.